Cardiovascular Side Effects of Psychostimulants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The short-term cardiovascular effects of methylphenidate (MPH) and Adderall (ADL) were examined in a clinic-based group of 195 youths, ages 4 to 17 years, treated at the University Hospitals of Cleveland, Case Western Reserve University.